Fully negative near-zero ultra-flat dispersion photonic crystal fibers in E+S+C+L band - Mao, Yucheng; Ma, Yiwu; Huang, Ying; Yang, Hua (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
We demonstrate a modified hexagonal three-layer air-hole photonic crystal fiber (PCF) which presents a good ability of dispersion management. The proposed PCF not only achieved an ultra-flattened all-negative dispersion characteristics of 0.15085 ps/(km·nm) fluctuation within the wavelength range of E+S+C+L wavelength band but also has been able to obtain other interesting features such as low confinement loss. Furthermore, the quadrilateral and octagonal structures are investigated to compare the superiority of different structures and analyze why we chose the hexagonal one.
Optica Applicata, Vol. 52, 2022, nr 4, s. 599-611
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; photonic crystal fiber; ultra-flattened dispersion; onfinement loss; dispersion management method; supercontinuum (SC) generation